When Do False Accusations Lead to False Confessions? Preliminary Evidence for a Potentially Overlooked Alternative Explanation. Issue 2 (14th March 2020) - Gubi-Kelm, Silvia; Grolig, Tuule; Strobel, Benjamin; Ohlig, Simon; Schmidt, Alexander F.
ABSTRACT: In the present study, we have taken a novel approach in confession research to investigate and compare situational as well as individual risk factors among false confessors and true deniers among imprisoned offenders who all had been falsely accused by the police. Furthermore, we report first data on self-reported false confession rates among German prison inmates. A semi-structured interview was conducted in four northern German prisons focusing on the interrogation situations in which the participants were falsely accused of a crime they had not committed. Of all respondents, 32% reported to have made a false confession, which is consistent with prior findings in the field. In line with the literature, prison inmates indicated fear of negative consequences and beliefs that the truth will come out as frequent reasons for false confessions. Notably, also strategic/instrumental purposes of their false confessions aimed at minimizing legal or personal repercussions due to the false accusations were revealed – although to a lesser degree. Implications from this preliminary alternative explanation based on strategic considerations for false confessions will be discussed in light of the common theoretical framework that focuses on psychological distress and deficits of false confessors.